Sonic hedgehog restrains the ubiquitin-dependent degradation of SP1 to inhibit neuronal/glial senescence associated phenotypes in chemotherapy-induced peripheral neuropathy via the TRIM25-CXCL13 axis - Ying Zou; Shu Wu; Qian Hu; Haoxian Zhou; Yuanlong Ge; Zhenyu Ju; Shengkang Luo (Journal of Advanced Research, 2025)
Introduction: Chemotherapy-induced peripheral neuropathy (CIPN) is a common complication that affects an increasing number of cancer survivors. However, the current treatment options for CIPN are limited. Paclitaxel (PTX) is a widely used chemotherapeutic drug that induces senescence in cancer cells. While previous studies have demonstrated that Sonic hedgehog (Shh) can counteract cellular dysfunction during aging, its role in CIPN remains unknown. Objectives: Herein, the aim of this study was to investigate whether Shh activation could inhibits neuronal/glial senescence and alleviates CIPN. Methods: We treated ND7/23 neuronal cells and RSC96 Schwann cells with two selective Shh activators (purmorphamine [PUR] and smoothened agonist [SAG]) in the presence of PTX. Additionally, we utilized a CIPN mouse model induced by PTX injection. To assess cellular senescence, we performed a senescence-associated β-galactosidase (SA-β-gal) assay, measured reactive oxygen species (ROS) levels, and examined the expression of P16, P21, and γH2AX. To understand the underlying mechanisms, we conducted ubiquitin assays, LC-MS/MS, H&E staining, and assessed protein expression through Western blotting and immunofluorescence staining. Results: In vitro, we observed that Shh activation significantly alleviated the senescence-related decline in multiple functions included SA-β-gal activity, expression of P16 and P21, cell viability, and ROS accumulation in DRG sensory neurons and Schwann cells after PTX exposure. Furthermore, our in vivo experiments demonstrated that Shh activation significantly reduced axonal degeneration, demyelination, and improved nerve conduction. Mechanistically, we discovered that PTX reduced the protein level of SP1, which was ubiquitinated by the E3 ligase TRIM25 at the lysine 694 (K694), leading to increased CXCL13 expression, and we found that Shh activation inhibited PTX-induced neuronal/glial senescence and CIPN through the TRIM25-SP1-CXCL13 axis. Conclusion: These findings provide evidence for the role of PTX-induced senescence in DRG sensory neurons and Schwann cells, suggesting that Shh could be a potential therapeutic target for CIPN.